Linking big data for cardiovascular health surveillance – opportunities and challenges using the CANHEART cohort - Anna Chu; Deirdre Hennessy; Sharon Johnston; Jacob Udell; Dennis Ko; Anam Khan; Jing Jia; Jack Tu (International Journal of Population Data Science, 2018)
Introduction Our increasing ability to link large population-based health administrative datasets to create ‘big data’ cohorts offers unique opportunities to conduct health and health services surveillance at lower costs than traditional methods using surveys or primary data collection. However, comparability of findings from big data with traditional methods is unknown.